Developing a 'Classroom as Community' Approach to Supporting Young Children's Wellbeing. Issue 4 (December 2017) - Whitington, Victoria; McInnes, Elspeth
INTRODUCING THE IDEA OF THE 'classroom as community', a class of six- to eight-year-old children engaged with a project, The Wellbeing Classroom (McInnes, Diamond & Whitington, 2014), which intended to support and advance their social and emotional development. This paper examines how the notion of 'classroom as community' informed the thinking and actions of the adults involved, and identifies six key elements of the approach employed. The teacher employed five strategies over a year: professional learning and reflection; building trust with children and modelling emotional self-regulation; teaching social skills across the day; accessing regular outreach worker support; and involving parents. Led by an upskilled teacher, the 'classroom as community' approach was found to have successfully supported children's social and emotional development, particularly those with difficulties. The project's reach included parents, thus extending its effects. This article reports on the significance of the concept of classroom as community to the project's success.